Development of an internet of things-based monitoring system for small vertical axis wind turbine - Prasetyo, Yuli; Triyono, Budi; Artono, Budi; Triwijaya, Santi; Khakim, Ainul; Ramadhan, Ade Nofa (Geuthèë Institute, 2025)
Small-scale wind turbines often face challenges related to low energy conversion efficiency and the lack of adequate monitoring and automatic protection systems against fluctuating weather and load conditions. This study presents the design and implementation of an Internet of Things (IoT)-based monitoring and protection system for a Small Vertical Axis Wind Turbine (VAWT). The system utilizes Arduino Uno and NodeMCU ESP8266 microcontrollers integrated with INA219, LM35, anemometer, infrared, and DC voltage sensors. Data acquisition and transmission are managed through Wi-Fi communication and displayed on the ThingSpeak web platform for real-time visualization. Experimental testing demonstrated that the system successfully measured and transmitted voltage, current, power, wind speed, temperature, and rotational speed parameters with an average data transmission latency of less than 3 seconds. The protection mechanism activated effectively under simulated abnormal conditions such as over-speed and over-temperature, automatically disconnecting the load to prevent turbine damage. The measurement accuracy for INA219 voltage and current sensors reached ±0.2 V and ±0.05 A, while temperature detection with LM35 had an average deviation of ±0.8 °C. The results indicate that the proposed IoT-based VAWT monitoring system is capable of providing reliable, low-cost, and real-time supervision suitable for small-scale renewable energy applications. Furthermore, it can be used as a learning prototype in vocational education to understand the integration of renewable energy and IoT technologies.